2015
DOI: 10.1186/s12889-015-2165-8
|View full text |Cite
|
Sign up to set email alerts
|

App use, physical activity and healthy lifestyle: a cross sectional study

Abstract: BackgroundPhysical inactivity is a growing public health concern. Use of mobile applications (apps) may be a powerful tool to encourage physical activity and a healthy lifestyle. For instance, apps may be used in the preparation of a running event. However, there is little evidence for the relationship between app use and change in physical activity and health in recreational runners. The aim of this study was to determine the relationship between the use of apps and changes in physical activity, health and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
2
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 34 publications
6
58
2
13
Order By: Relevance
“…Tailored feedback to coach and motivate was also viewed as important (20). In another study, runners who used an app to train for a future running event reported improved self-esteem, feeling athletic, losing weight, and promoting running among others (21). These results suggest the potentially useful role of apps for longer-term behavior change.…”
Section: Introductionmentioning
confidence: 87%
“…Tailored feedback to coach and motivate was also viewed as important (20). In another study, runners who used an app to train for a future running event reported improved self-esteem, feeling athletic, losing weight, and promoting running among others (21). These results suggest the potentially useful role of apps for longer-term behavior change.…”
Section: Introductionmentioning
confidence: 87%
“…4 Healthcare apps can also facilitate access to a patient medication regimen and can be used to arrange an appointment with a physician. Apps can be utilised to educate patients and help change their behaviour for instance, healthy food apps can be used to monitor an individual's behaviour related to calorie intake and provide advice about healthy eating habits including fat and carbohydrate content of different food items [12,3]. Recent advances in mobile technologies have opened new approaches to support healthcare delivery and patient education.…”
Section: Introductionmentioning
confidence: 99%
“…They are used on a daily basis to communicate with friends and relatives, perform online shopping, read news and for monitoring health related parameters including diet, exercise and sleep. Such apps can have a positive impact on promoting improved health and wellbeing and are increasingly being embraced by health care professionals [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…For participants who were 16 km runners, app use was positively related to eating healthier and reporting a higher chance of maintaining the physical activity. They also found that app users often encouraged others to engage in running compared to non-app users (Dallinga et al, 2015). This finding could be useful for families as parents may encourage their children to participate in physical activity.…”
Section: Nutrition Self-efficacy Themesmentioning
confidence: 75%
“…Researchers using a cross sectional design looked at how mobile apps may be a tool to encourage physical activity and a healthy lifestyle (Dallinga, Mennes, Alpay, Bijwaard, & de la Faille-Deutekom, 2015).…”
Section: Nutrition Self-efficacy Themesmentioning
confidence: 99%